SPECIFICITY OF TEACHING JUNIOR STUDENTS WITH VISUAL IMPAIRMENT - Matveyeva Nataliіa (Mountain School of Ukrainian Carpaty, 2019)
The article emphasizes that today the problem of teaching, upbringing and development of people with special educational needs, and in particular with visual impairment, is especially relevant. As the number of individuals with this nosology grows annually, as evidenced by the statistics of the Ministry of Health of Ukraine, the need to find new approaches to youth education and upbringing is updated; the choice of non-traditional forms, methods, methods and means of teaching children of school age with visual impairment. The solution to this and a number of other accompanying tasks is to create a comfortable environment in which students would be comfortable with other students, to successfully learn, to master the vital competences, to develop their skills and abilities, to realize their creative potential. Instead, it is particularly important to overcome a number of difficulties that occur in the process of introducing an inclusive model of learning, as they preclude the inhibition of this process as a whole and lead to a variety of impediments to the life of students. The purpose of the study was to highlight a number of peculiarities of this category of junior pupils, to establish their real opportunities for exercising in school and to determine the specifics of the teaching and educational activities of teachers in working with them; establish a list of requirements for the activities of the teacher in order to prevent the emergence of certain difficulties in the learning process; to establish the level of readiness of pupils with visual impairments before studying in a general educational institution. In the process of our study, we used the following methods, namely: theoretical (working out literary sources, normative-legal basis of inclusive education); empirical (questionnaires, surveys, observations, ethical conversations, rankings, expert evaluation, methods of statistical processing of data). The results of our study once again confirmed the already existing hypotheses of a number of scholars that, in the case of the inclusion of children with different types of nosology’s for studying in secondary schools, it is necessary to carefully examine their peculiarities and possibilities by timely diagnosing the individual possibilities, factors, learning levels, peculiarities of students; outline the main ways to increase the effectiveness of creating an inclusive environment in an educational institution; To carry out innovative activities for the provision of quality educational services for younger students with visual impairment.